Prevalence of awareness Hazards and Dependence of Smartphone Usage among Students of the Faculty of Computer and Information Technology at Sanaa University: مدى انتشار الوعي بمخاطر استخدام الهاتف الذكي والاعتماد عليه بين طلاب كلية الحاسوب وتكنولوجيا المعلومات بجامعة صنعاء - Sarah Abdulkhaleq Ali Sallam, Intesar Yahya Hussin Qahta, Muneer Abduallah Saeed Hazaa (Journal of engineering sciences and information technology, 2019)
Background: Mobile phone addiction is a type of technological addiction. With regard to large number of mobile users especially among college students in Yemen, dependence of mobile phone is attracting increasing concern. This study examines validity and reliability of the Yemeni college student version of mobile phone addiction scale in college students. Object: To study the addiction behavior and awareness of mobile phone on Electromagnetic Radiation (EMR) among a college student sample. Material and method: A cross-sectional study was conducted among undergraduate college students aged ≥18 years studying at Sana’a University, Sana’a, Yemen, from November 1st 2017 until Feb 2nd, 2018.A pretested self-administered questionnaire was used for data collection. The study instrument comprised eight segments, namely, informed consent information, consent acceptance page, demographic details, habituation, mobile phone fact and EMR, mobile phone awareness, psychomotor analysis, Data analyzed using IBM SPSS Version 17. Results: Totally, 204 individuals participated in the study, of which 42.3% were males and 57.7% were females, between the age group of 20 ->31 years. Nearly 75.9% of the respondents were between the age group of 21 and 25 years. The mean age of the study participants was 22.88 (standard error = 0.24) years.. Around 55%of the study participants use mobile phone for an hour (approximately) and remaining use it for more than an hour. Nearly36.7% checking mobile phones in between sleep, while 27.1% felt inconvenience with mobile phone use. Majority using mobile phone for communication purposes (87.8%), photo shooting (59.7%), entertainment (58.2%), and educational purposes (43.8%). The study results indicate that 86.8% of the participants are aware about EMR and 82.6% of the study participants are aware about the dangers of EMR. Conclusion: Mobile phone use with increasing adoption promotes an addiction-like behavior that is evolving a public health problem in a large proportion in Yemen.